Hypolipidemic Effects and Preliminary Mechanism of Chrysanthemum Flavonoids, Its Main Components Luteolin and Luteoloside in Hyperlipidemia Rats - Jihan Sun; Zhaodan Wang; Lin Chen; Guiju Sun (MDPI AG, 2021)
This study aimed to investigate the key constituents and preliminary mechanism for the hypolipidemic activity of chrysanthemum flavonoids. Hyperlipidemia (HPL) rats were divided into five groups: the model control group (MC); Chrysanthemum flavone intervention group (CF); luteolin intervention group; luteoloside intervention group and simvastatin intervention group. The body weight, organ coefficient, serum lipids, antioxidant activity, and lipid metabolism enzymes were detected. Hematoxylin and eosin (H&E) staining was used to observe the liver and adipose tissue. Chrysanthemum flavonoids, luteolin, and luteoloside can reduce the weight and levels of total cholesterol (TC), triglycerides (TG), and LDL-C, and increase the level of HDL-C in the blood and reduce liver steatosis. Indicators of liver function (AST, ALT, and ALP) improved. The antioxidant activity (GSH-Px, CAT, SOD) and enzymes associated with lipid catabolism (FAβO, CYP7A1, and HL) increased, while lipid peroxidation products (MDA) and enzymes associated with lipid synthesis (FAS, HMG-CoA, and DGAT) decreased. Chrysanthemum flavonoids had a better effect on the antioxidant level and lipid metabolism-related enzyme activity. There was no significant difference in the effects of the chrysanthemum flavonoids, luteolin, and Luteoloside on improving blood lipids and hepatic steatosis-mechanisms that may be related to antioxidant levels and regulating enzymes involved in the metabolism of fatty acids, cholesterol, and triglycerides in the liver. However, chrysanthemum flavonoids had a stronger antioxidant and lipid metabolism regulation ability, and the long-term effects may be better.